Penggunaan kemasan plastik polietilen biodegradable terhadap umur simpan gula kelapa: The Use of Biodegradable Polyethylene Plastic on The Shelf Life of Palm Sugar - Aminullah Aminullah; Nurfauziah Hadiati; Titi Rohmayanti (Pro Food, 2022)
Palm sugar is a group of brown sugar in the form of block or granule that can be packaged using polyethylene plastik. This study aimed to determine the shelf life of blocked and granulated palm sugar stored in conventional and biodegradable polyethylene plastik packaging. This study consisted of two main stages: preparation and shelf-life testing using the accelerated shelf-life testing method with a critical moisture content approach. The parameters included the sample's initial moisture content, dry weight, critical moisture content, packaging area, and packaging permeability before determine the shelf-life of palm sugar products. Statistical analysis showed that palm sugar stored in biodegradable polyethylene packaging and granulated palm sugar had a longer shelf life than palm sugar stored in conventional polyethylene. Granulated palm sugar packaged in biodegradable polyethylene plastik has the most extended shelf life, 1192 days, while blocked palm sugar in conventional polyethylene packaging has the shortest shelf life, 366 days.